Dapatkah Putusan Perkara Pidana Dijadikan Sebagai Dasar Peninjauan Ulang Putusan Mahkamah Konstitusi - Hartoyo, Dwijoyo; Rizkianto, Kus; Mahardika, Dinar; Pratama, Erwin Aditya (Diktum: Jurnal Ilmu Hukum, 2021)
The purpose of this paper is to review the decision of the Constitutional Court made due to the criminal act of bribery on constitutional judges. Based on the Constitution of the Republic of Indonesia of 1945 in article 24 C and Article 10 paragraph (1) of Law Number 24 of 2003 concerning the Constitutional Court states that the Constitutional Court has the authority to adjudicate at the first and last level whose decision is final, namely a decision that immediately obtains permanent legal force since it is pronounced and no legal remedy can be taken. However, what would be the legal consequences if the Constitutional Court's decision was made on the basis of the criminal act of bribery. This research is a conceptual study that examines the thoughts of reviewing the Constitutional Court's decision on the existence of a bribery crime. The results of this study include (1) the legal consequences if the decision of the Constitutional Court is made on the basis of the criminal act of bribery is Null and Void with all its consequences, and (2) The decision of the criminal case may be used as a basis for review of the decision of the Constitutional Court.